PENGARUH AUDIT INVESTIGASI TERHADAP PENGUNGKAPAN FRAUD DI INDONESIA - Ayu Wulandari; Melandari Eka Putri; Yeni Marlina (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2021)
Fraud is a problem that continues to date. Because no company or institution is immune from this fraud, companies or government agencies are required to build internal controls. with the role of auditing in the company, it can help the government or company to minimize the occurrence of weaknesses, errors and risks of theft. This is what motivates the author to explain more about the role of audit investigations. The method in this research is to use qualitative research methods with secondary data sources from the Association of Cerified Fraud Examiners, then the data collection process is carried out using documentation techniques which means that the data comes from the internet and books that have discussed the role of audit investigations. The results of this study. The role of internal audit is as a supervisor against fraud. Internal audit is responsible for helping management prevent fraud by testing and evaluating the reliability and effectiveness of controls in line with the potential risk of fraud in various segments. With the audit, it is hoped that the implementation of a country that is clean and free from corruption, collusion and nepotism is expected.